Improved hybrid boundary solution for shell elements. (October 2016) - Naga, Taha H.A.; Rashed, Youssef F.
Abstract: In this paper, a new finite element for shell structures is developed using an improved hybrid boundary solution. First the variational boundary integral equation for shear-deformable plate bending problems is developed based on quadratic boundary elements. Hence such a formulation is coupled to a similar formulation for 2D plane stress problems to produce the developed shell elements. Numerical examples are presented to demonstrate the accuracy and validity of the proposed formulation.